Zooming In : From Aggregate Volatility to Income Distribution - Calderón, César; Yeyati, Eduardo Levy (2012)
In contrast with a growing literature on the drivers of aggregate volatility in developing countries, its consequences in terms of individual incomes have received less attention. This paper looks at the impact of cyclical output fluctuations and extreme output events (crises) on unemployment, poverty, and inequality. The authors find robust evidence that aggregate volatility has a regressive, asymmetric, and non linear impact, as reflected in the strong influence of extreme output drops. The findings show that, in addition to the mitigating role of personal wealth, public expenditure and labor protection exert a similar benign effect. These findings are in line with the income substitutions view of social safety nets, and cast a new light on the value of social programs and labor market regulation in crisis prone developing countries.